PERAN MEDICOLEGAL FORENSIK DALAM PEMBUKTIAN TINDAK PIDANA - Mohamad Alfian Koyo; Sumiyati B.; Suardi Rais (Fakultas Hukum Universitas Ichsan Gorontalo, 2024)
This research aims (1) to find out the role of medicolegal forensics in proving criminal acts and (2) to find out the inhibiting factors of medicolegal forensics in proving criminal acts. The type of research employed is empirical research, namely a legal method that functions to see the law in real terms and examine how the law works in the community. It is research with field data as the main source, such as the results of interviews and observations. The research results indicate that (1) The role of medicolegal forensics in proving criminal acts in Gorontalo is very necessary for the role of medicolegal forensics installations. But, in this case, the proof carried out by the medicolegal forensics’ installation is still ineffective because, in the field, forensic experts in Gorontalo are still limited. (2) The inhibiting factors of medicolegal forensics in proving are quite serious, namely starting from the lack of human resources and not supporting infrastructure and facilities. It interferes with the proving process. This research recommends that (1) The police medics and Health Unit of Gorontalo Regional Police should add forensic experts and forensic personnel to support the acceleration of proofs in Gorontalo, and (2) The two parties mentioned above can complete the facilities and infrastructure in the Bhayangkara Hospital of Gorontalo to support the proof of criminal acts.